High Representation of Archaea Across All Depths in Oxic and Low-pH Sediment Layers Underlying an Acidic Stream - Distaso, Marco A.; Bargiela, Rafael; Brailsford, Francesca L.; Williams, Gwion B.; Wright, Samuel; Lunev, Evgenii A.; Toshchakov, Stepan V.; Yakimov, Michail M.; Jones, David L.; Golyshin, Peter N.; Golyshina, Olga V. (Frontiers in Microbiology, 2020)
Parys Mountain or Mynydd Parys (Isle of Anglesey, UK) is a mine-impacted environment, which accommodates a variety of acidophilic organisms. Our previous research of water and sediments from one of the surface acidic streams showed a high proportion of archaea in the total microbial community. To understand the spatial distribution of archaea, we sampled cores (0-20 cm) of sediment and conducted chemical analyses and taxonomic profiling of microbiomes using 16S rRNA gene amplicon sequencing in different core layers. The taxonomic affiliation of sequencing reads indicated that archaea represented between 6.2% and 54% of the microbial community at all sediment depths. Majority of archaea were associated with the order Thermoplasmatales, with the most abundant group of sequences being clustered closely with the phylotype B_DKE, followed by ‘E-plasma’, ‘A-plasma’, other yet uncultured Thermoplasmatales with Ferroplasma and Cuniculiplasma spp. represented in minor proportions. Thermoplasmatales were found at all depths and in the whole range of chemical conditions with their abundance correlating with sediment Fe, As, Cr and Mn contents. The bacterial microbiome component was largely composed in all layers of sediment by members of the phyla Proteobacteria, Actinobacteria, Nitrospirae, Firmicutes, uncultured Chloroflexi (AD3 group), and Acidobacteria. This study has revealed a high abundance of Thermoplasmatales in acid mine drainage-affected sediment layers and pointed at these organisms being the main contributors to carbon, and probably to iron and sulfur cycles in this ecosystem.